Single nucleotide polymorphism profiles of canine T-cell and null-cell lymphomas - Sirivisoot, Sirintra; Kasantikul, Tanit; Techangamsuwan, Somporn; Rungsipipat, Anudep (Frontiers in Veterinary Science, 2024)
The histopathological classification of T-cell lymphoma (TCL) in humans has distinctive mutational genotyping that suggests different lymphomagenesis. A similar concept is assumed to be observed in dogs with different TCL phenotypes.Objective: This study aimed to identify the previously reported single nucleotide polymorphisms (SNPs) from both human beings and dogs in canine TCLs and null-cell lymphomas (NCLs) and to design compatible oligonucleotides from each variant based on the multiplex polymerase chain reaction. Method: Genomic DNA was extracted from 68 tumor specimens and five buffy coat samples from dogs with TCL. Four TCL subtypes and NCL were analyzed in 44 SNPs from 21 genes using the MassARRAY. Results: The greatest incidence of SNPs observed in all TCL subtypes and NCL were SATB1 c.1259A>C, KIT c.1275A>G, SEL1L c.2040+200C>G, and TP53 c.1024C>T, respectively. Some SNP locations were statistically significantly associated with NCL including MYC p.S75F (p = 0.0003), TP53 p.I149N (p = 0.030), PDCD1 p.F37LX (p = 0.012), and POT1 p.R583* (p = 0.012).Each TCL histological subtype and NCL is likely to contain distinctive mutational genetic profiles, which might play a role in lymphoma gene-risk factors and might be useful for selecting therapeutic target drugs for each canine patient.